ETANÓLICO DE EUPHORBIA CANDELABRUM WELW. EX HIERN “CANDELABRO” - Castilla Villagaray, Iris G. (2024)
It has been proven that one of the main causes of melanoma is exposure to Ultraviolet Radiation (RUV), so the use of photoprotectors is very important. The objective was to demonstrate the in vitro photoprotective activity of a cream obtained from the ethanolic extract of Euphorbia candelabrum Welw. ex Hiern “chandelier”, the extract was obtained by the maceration method, a phytochemical screening was carried out to identify the secondary metabolites, the antioxidant activity of the extract was verified by the DPPH and FRAP methods, creams were prepared at the concentrations of 1%, 3% and 5% and the relevant quality controls were carried out, the in vitro photoprotective activity was evaluated by the method described by Mansur. The antioxidant activity by the DPPH method showed an IC50 of 0.09836 mg/mL, and by the FRAP method it was reported that 1 mg/mL of extract is equivalent to 1.04 mmol of TROLOX. The extract showed an SPF of 17.70, while the 1%, 3% and 5% creams obtained an SPF of 4.81, 11.34 and 25.97 respectively. Concluding that the 5% cream obtained a high SPF according to the COLIPA classification, demonstrating that it has UVB photoprotective activity.